Hybrid de novo and haplotype-resolved genome assembly of Vechur cattle — elucidating genetic variation - Muthusamy, Poorvishaa V.; Vakayil Mani, Rajesh; Kumari, Shivani; Kaur, Manpreet; Bhaskar, Balu; Raghavan Pillai, Rajeev; Sajeev Kumar, Thankappan; Anilkumar, Thapasimuthu Vijayamma; Singh, Nongmaithem Sadananda (Frontiers in Genetics, 2024)
Cattle contribute to the nutritional needs and economy of a place. Performance and fitness depends on the response and adaptation to local climatic conditions. Genomic and genetic studies are important for advancing cattle breeding and availability of relevant reference genomes are essential. In the present study, the genome of a Vechur calf was sequenced on both short-read illumina and long-read nanopore platforms. Hybrid de novo assembly approach was deployed to obtain an average contigs length of 1.97 Mbp and N50 of 4.94 Mbp. Using a short-read genome sequence of the corresponding sire and dam, a haplotype-resolved genome was also assembled. In comparison to the taurine reference genome, we found 28,982 autosomal structural variants, 16,926,990 SNVs with 883,544 SNVs homozygous in the trio samples. Many of these SNPs have been reported to be associated with various QTLs including growth, milk yield, and milk fat content which are crucial determinants of cattle production. Further, population genotype data analysis indicated that the present sample belongs to an Indian cattle breed forming a unique cluster of Bos indicus. Subsequent FST analysis revealed differentiation of the Vechur cattle genome at multiple loci, especially those regions related to whole body growth and cell division especially IGF1, HMGA2, RRM2, and CD68 loci suggesting a possible role of these genes in its small stature and better disease resistance capabilities in comparison with the local crossbreeds. This provides an opportunity to select and engineer cattle breeds optimized for local conditions.